Federalism and ethnic conflict regulation in India and Pakistan - Adeney, Katharine; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2007)
Katharine Adeney demonstrates that institutional design is the most important explanatory variable in understanding the different intensity and types of conflict in the two countries rather than the role of religion. Adeney examines the extent to which previous constitutional choices explain current day conflicts.
Keywords: Political science; Ethnology -- Asia; Asia -- Politics and government; International relations